Dampak Inflasi Kebutuhan Pokok Terhadap Pola Pengeluaran Konsumsi Rumah Tangga Indonesia : Pendekatan Quadratic Almost Ideal Demand System (Quaids) - Kibri Mananja; Joan Marta (Universitas Negeri Padang, 2024)
This research aims to determine the impact of basic needs inflation on household expenditure patterns in Indonesia. This research is quantitative research using secondary data from the 2020 BPS National Socio-Economic Survey. The analysis used is descriptive analysis and inductive analysis. In inductive analysis, this research uses the QUAIDS (Quadratic Almost Ideal Demand System) approach to analyze the impact of rising prices of basic necessities on household consumption expenditure patterns in Indonesia. The results of this research show that the increase in prices of basic necessities has a negative and significant impact on several types of household consumption expenditure, namely food, transportation and communication. Household expenditure on food is the one that suffers the most if there is an increase in the price of basic necessities, followed by communications and transportation expenditure.